Design and Simulation of Thin-Film Silicon Quantum Well Photovoltaic Cell - R. Sircar; B. Tripathi; S. Gupta (Журнал нано- та електронної фізики)
A new thin-film silicon photovoltaic cell could be designed by inserting quantum well layers in the intrinsic region. Calculations show the improvement in spectral absorption due to the quantum well layer insertion. This article reports the design parameters and enhanced spectral absorption for a newly designed thin-film silicon quantum well photovoltaic cell.